Evolution of astrocytes: From invertebrates to vertebrates - Falcone, Carmen (Frontiers in Cell and Developmental Biology, 2022)
The central nervous system (CNS) shows incredible diversity across evolution at the anatomical, cellular, molecular, and functional levels. Over the past decades, neuronal cell number and heterogeneity, together with differences in the number and types of neuro-active substances, axonal conduction, velocity, and modes of synaptic transmission, have been rigorously investigated in comparative neuroscience studies. However, astrocytes, a specific type of glial cell in the CNS, play pivotal roles in regulating these features and thus are crucial for the brain’s development and evolution. While special attention has been paid to mammalian astrocytes, we still do not have a clear definition of what an astrocyte is from a broader evolutionary perspective, and there are very few studies on astroglia-like structures across all vertebrates. Here, I elucidate what we know thus far about astrocytes and astrocyte-like cells across vertebrates. This information expands our understanding of how astrocytes evolved to become more complex and extremely specialized cells in mammals and how they are relevant to the structure and function of the vertebrate brain.